2023
DOI: 10.3390/cancers15020390
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Prognosis of Alpha-Fetoprotein and Des-Gamma-Carboxy Prothrombin Double-Negative Hepatocellular Carcinoma at Baseline in Higher BCLC Stages

Abstract: Alpha-fetoprotein (AFP) and des-gamma-carboxyprothrombin (DCP) are widely used as tumor markers to diagnose hepatocellular carcinoma (HCC). Some advanced HCCs demonstrate neither AFP nor DCP. This study investigated the characteristics and prognosis of AFP (< 20 ng/mL) and DCP (< 40 mAU/ml) double-negative HCC (DNHC) in higher-stage HCC. Between April 2012 and March 2022, 419 consecutive patients were enrolled with newly diagnosed HCC and 372 patients were selected that were diagnosed by histopathology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…More recently, some studies indicated that locoregional therapy was selected more frequently in DNHC patients, and the 3-year recurrence rate of these patients was approximately 55%. 19 , 20 However, prediction models of recurrence for DNHC patients treated with local ablation are still insufficient at present. Thus, our research serves to develop and verify a dependable nomogram for this group of patients with the aim of guiding the decision of clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, some studies indicated that locoregional therapy was selected more frequently in DNHC patients, and the 3-year recurrence rate of these patients was approximately 55%. 19 , 20 However, prediction models of recurrence for DNHC patients treated with local ablation are still insufficient at present. Thus, our research serves to develop and verify a dependable nomogram for this group of patients with the aim of guiding the decision of clinicians.…”
Section: Introductionmentioning
confidence: 99%